PENGARUH KOMPETENSI DAN PRESTASI KERJA TERHADAP PROMOSI JABATAN PADA (PDAM) TIRTAULI CABANG I PEMATANGSIANTAR - Prasetio, Edy Teguh; Lie, Darwin; Butarbutar, Marisi; Putri, Debi Eka (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2019)
The objectives of this study are: 1) To find out the description of competency, work performance and promotion in the Regional Water Supply Company (PDAM) Tirtauli Branch I Pematangsiantar. 2) To find out the effect of competency and work performance on promotion in the Regional Water Supply Company (PDAM) Tirtauli Branch I Pematangsiantar both simultaneously and partially. The results of the study can be summarized as follows: 1) Competence, work performance and promotion are good. 2) The results of the regression analysis are Ŷ = 3.943 + 0.770X1 + 0.345X2 meaning that competency and work performance have a positive and significant effect on job promotion. 3) The results of the correlation analysis obtained nilair = 0.787, meaning that there is a strong and positive relationship between competence and work performance with promotion. 4) Obtained the coefficient of determination R = 0.619 means that the high and low of promotion can be explained by competence and work performance by 39.0%. 5) The research hypothesis H0 is rejected, meaning that competence and work performance have a positive and significant effect on job promotion in the Regional Water Supply Company (PDAM) Tirtauli Branch I Pematangsiantar both simultaneously and partially. Keywords: Competence, Job Performance, and Job Promotion